The EU in the 21st Century Challenges and Opportunities for the European Integration Process - Ramiro Troitiño, David; Kerikmäe, Tanel; de la Guardia, Ricardo Martín; Pérez Sánchez, Guillermo Á. (Springer International Publishing : Imprint: Springer, 2020)
X, 317 p. 8 illus., 4 illus. in color.